Mitigating the relativistic laser beam filamentation via an elliptical beam profile. - Huang, T; Zhou, C; Robinson, A; Qiao, B; Zhang, H; Wu, S; Zhuo, H; Norreys, P; He, X (American Physical Society, 2015)
It is shown that the filamentation instability of relativistically intense laser pulses in plasmas can be mitigated in the case where the laser beam has an elliptically distributed beam profile. A high-power elliptical Gaussian laser beam would break up into a regular filamentation pattern-in contrast to the randomly distributed filaments of a circularly distributed laser beam-and much more laser power would be concentrated in the central region. A highly elliptically distributed laser beam experiences anisotropic self-focusing and diffraction processes in the plasma channel ensuring that the unstable diffractive rings of the circular case cannot be produced. The azimuthal modulational instability is thereby suppressed. These findings are verified by three-dimensional particle-in-cell simulations.